Flow field analysis of a pentagonal-shaped bridge deck by unsteady RANS. Issue 1 (1st January 2016) - Haque, Md. Naimul; Katsuchi, Hiroshi; Yamada, Hitoshi; Nishio, Mayuko
ABSTRACT: Long-span cable-stayed bridges are susceptible to dynamic wind effects due to their inherent flexibility. The fluid flow around the bridge deck should be well understood for the efficient design of an aerodynamically stable long-span bridge system. In this work, the aerodynamic features of a pentagonal-shaped bridge deck are explored numerically. The analytical results are compared with past experimental work to assess the capability of two-dimensional unsteady RANS simulation for predicting the aerodynamic features of this type of deck. The influence of the bottom plate slope on aerodynamic response and flow features was investigated. By varying the Reynolds number (2 × 10 4 to 20 × 10 4 ) the aerodynamic behavior at high wind speeds is clarified.